doc
dy
.
solve
ytz
Z+x
dz
xty
POJ -
2)
Answers
Answered by
0
Answer:
Given,
dx / (y + z) = dy / (- x - z) = dz / (x - y)
So, it can also be expressed as:
dx / (y + z) = (dy + dz) / (- x - z + x - y)
dx / (y + z) = (dy + dz) / (- y - z)
dx = - (dy + dz)
dx + dy + dz = 0
Taking integration of both sides, we get:
[integration] (dx + dy + dz) = k, where k is a constant of integration.
[integration] dx + [integration] dy + [integration] dz = k
(x + y + z) = k
Similar questions
Math,
2 months ago
English,
2 months ago
Math,
5 months ago
Social Sciences,
5 months ago
Math,
1 year ago